Social Networks and Entrepreneurship. Evidence from a Historical Episode of Industrialization (2018)
First, modern economic growth brings a more cohesive society. Second, modern economic growth brings long-term reductions in fertility with potential short-term increases. Third, initial barriers to social interactions could explain the timing of modern economic growth arrival. Fourth, the timing of modern economic growth arrival could explain current output levels. I exploit different data sources to offer evidence in support of these predictions.